Analisis Rasio Solvabilitas (DAR, DER, CAR, LTDER, LTDAR) dalam Menilai Kinerja Keuangan pada PT Bank Central Asia Tbk Tahun 2019-2022 - Ina Urifah; Putri Kurnia Sari; Anggita Farah Adiba; Renny Oktafia (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study aims to analyze the solvency ratio at PT Bank Central Asia by looking at the percentage of the ability to pay debts against assets and equity with indicators of debt to equity ratio, debt to asset ratio, capital adequacy ratio, long term debt to equity ratio, and long term debt to asset ratio. This research method uses a descriptive method with a quantitative approach. The data used is secondary data obtained from the annual report data of PT Bank Central Asia in 2019-2022. The results of this study indicate that overall it is declared sovable. For 4 years (2019-2022) PT Bank Central Asia in the analysis of capital adequacy ratio, long term debt to equity ratio, long term debt to asset ratio is in accordance with established industry standards, although in the analysis of debt to asset ratio and debt to equity ratio shows numbers above industry standards.